Predicting Timber Demand for the Shipyard Industry in Batang, Central Java, Indonesia Using System Dynamics Modeling - Deniska Adi Prasetyo; Djoko Soeprijadi; Slamet Riyanto (Jurnal Ilmu Kehutanan, 2026)
Indonesia’s wooden shipbuilding industry faces pressure from rising fisheries targets and unstable timber supplies. Batang Regency, a prominent shipyard cluster in Indonesia, relies on tropical hardwoods such as bengkirai and merbau as the main raw material for shipbuilding. More fishing, under Maximum Sustainable Yield (MSY) and Total Allowable Catch (TAC) policies, will strain timber resources. This research developed a dynamic simulation model to estimate future timber demand for Batang’s wooden shipyards, using data from 21 shipyards and fisheries, timber, MSY, and TAC statistics (2014–2018). Implemented in Powersim Studio 10 and validated using the Mean Absolute Percentage Error (MAPE) by comparing simulated outputs with historical observations. The model estimated cumulative timber use of 52,035 m3 (an average of 10,407 m3/year) for 2014–2018. Projections show demand rising to 42,293 m3 by 2035 (0.93% of national output), with high accuracy (MAPE <5%). Integrating fisheries and timber data, the model supports sustainable planning for Indonesia’s wooden shipbuilding industry.